The Effect of Vagal Nerve Stimulation on the Quality of Life in Pediatric Cases - Hande Gazeteci Tekin; Sezen Köse; Sarenur Gökben; Serpil Erermiş; Tuncer Turhan; Hasan Tekgül; Sanem Yılmaz; Gül Serdaroğlu (Galenos Yayinevi, 2017)
Aim: To evaluate the value of vagal nerve stimulation (VNS) in improving the quality of life, seizure frequency and mood in children with pharmacoresistant epilepsy. Materials and Methods: Eleven pharmacoresistant epileptic children implanted with the VNS therapy device between 2010-2014 were included in this prospective longitudinal study. Clinical assessment for the Diagnostic and Statistical Manual of Mental Disorders-IV psychiatric disorders, schedule for affective disorders, and schizophrenia for school children were applied. Childhood Depression Inventory (CDI), Beck Depression Inventory (BDI) were filled. Child Behavior Checklist (CBCL) and the Pediatric Quality of Life Inventory (PedsQL) were filled in by parents before the implantation. All of these tests were repeated in the first and second year of implantation. Results: Mean age at the first implantation of the VNS therapy device was 11.5 (2.5-16). Mean age was 13.9 (2.5-18) years. Mean duration of epilepsy prior to VNS implantation was 6.6 years, and VNS usage period was 30.4 months (10-96). International League Against Epilepsy classification of predominant seizure type was partial in seven, and generalized in four patients. Decrease in the number of seizures was 42% and 43% in the first and the second year respectively. While four of 11 patients had no psychopathology, different problems were determined in seven patients. There was no statistically significant difference between the scores of CDI/BDI, scores of CBCL and PedsQL prior to implantation, and also did not differ 1 year and 2 years after implantation. Conclusion: VNS is partially effective in controlling drug-resistant epilepsy. Although a positive effect on depression and quality of life is reported in literature, the results of this study were not statistically significant. We think that the scores of depression inventory should gradually decrease in years as it is reported for seizure frequency.